Safety of Neoadjuvant Immunotherapy in Resectable Cancers: A Meta-Analysis - Xu, Jiawei; Wu, Yongfeng; Xu, Yuedan; Qiu, Yuan; Li, Xiaobo; Song, Yumeng; Zhang, Ling (Frontiers in Immunology, 2022)
Background Neoadjuvant immunotherapy has preliminarily been effective in multiple resectable cancers. However, its safety is still largely unknown. Methods A systematic literature search was conducted in PubMed, Embase, Web of Science, and Cochrane Library up to February 28th, 2021. Pooled incidence and risk ratio (RR) of adverse events were calculated using the R software. Results Twenty-eight studies involving 2863 patients were included. First, the incidence for all-grade treatment-related adverse events (trAEs) was 94% (95% CI, 81%-98%), with 43% (95% CI, 24%-64%) for high-grade trAEs. For different treatment groups, neoadjuvant immune checkpoint inhibitors (ICIs) plus chemotherapy was associated with a higher incidence of all-grade [99% (95% CI, 98%-99%) vs. 76% (95% CI 47%-92%); P < 0.001] and high-grade [80% (58%-92%) vs. 15% (9%-24%); P < 0.001] trAEs compared with neoadjuvant ICIs alone. The most common high-grade trAEs were lipase increased (5%; 95% CI, 2%-10%), colitis (3%; 95% CI, 0-7%) and transaminitis (3%; 95% CI, 0-7%) for neoadjuvant ICIs, and neutropenia (53%; 95% CI, 31%-74%), anemia (8%; 95% CI, 3%-15%) and AST increased (4%; 95% CI, 2%-7%) for neoadjuvant ICIs plus chemotherapy. Furthermore, the incidence rates of progressive disease while on treatment, treatment-related surgical delays and deaths were 6% (95% CI, 4%-10%), 3.2% (12 of 377 patients) and 0.47% (5 of 1075 patients), respectively. Conclusion Compared with neoadjuvant ICIs alone, neoadjuvant ICIs plus chemotherapy had a higher incidence of trAEs. In addition, neoadjuvant immunotherapy had a low rate of progressive diseases, surgical delays and deaths.